PENGARUH MOTIVASI BELAJAR, GAYA BELAJAR, DAN LINGKUNGAN BELAJAR PADA HASIL BELAJAR EKONOMI DI SMA NEGERI 1 WRINGINANOM GRESIK - Farid, Muhammad Miftah (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aims to analyze the influence of learning motivation, learning styles and learning environments on learning outcomes economy partially or simultaneously. The population in this study is IPS students a total of 314 people and a total sample of 153 students in SMA Negeri 1 Wringinanom Gresik. The data collection techniques used were questionnaires and documentation. Analysis method using multiple linear regression techniques. The results showed that the learning motivation, learning style and learning environment partially positive significant effect on learning outcomes. Learning motivation, learning style and the learning environment simultaneously positive significant effect on learning outcomes